Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex], we can use the quadratic formula. The quadratic formula for solving equations of the form [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, we identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] from the given equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex]. Specifically:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
- [tex]\( c = -24 \)[/tex]
Now, substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot (-24)}}{2 \cdot 1} \][/tex]
Simplify the expression step-by-step:
1. Compute the discriminant:
[tex]\[ (-2)^2 - 4 \cdot 1 \cdot (-24) = 4 + 96 = 100 \][/tex]
2. Take the square root of the discriminant:
[tex]\[ \sqrt{100} = 10 \][/tex]
3. Apply the quadratic formula:
[tex]\[ x = \frac{2 \pm 10}{2} \][/tex]
This gives us two potential solutions:
[tex]\[ x = \frac{2 + 10}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ x = \frac{2 - 10}{2} = \frac{-8}{2} = -4 \][/tex]
Thus, the solutions to the equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex] are:
[tex]\[ x = -4 \quad \text{and} \quad x = 6 \][/tex]
So, the correct answer is:
B. [tex]\( -4, 6 \)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, we identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] from the given equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex]. Specifically:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
- [tex]\( c = -24 \)[/tex]
Now, substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot (-24)}}{2 \cdot 1} \][/tex]
Simplify the expression step-by-step:
1. Compute the discriminant:
[tex]\[ (-2)^2 - 4 \cdot 1 \cdot (-24) = 4 + 96 = 100 \][/tex]
2. Take the square root of the discriminant:
[tex]\[ \sqrt{100} = 10 \][/tex]
3. Apply the quadratic formula:
[tex]\[ x = \frac{2 \pm 10}{2} \][/tex]
This gives us two potential solutions:
[tex]\[ x = \frac{2 + 10}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ x = \frac{2 - 10}{2} = \frac{-8}{2} = -4 \][/tex]
Thus, the solutions to the equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex] are:
[tex]\[ x = -4 \quad \text{and} \quad x = 6 \][/tex]
So, the correct answer is:
B. [tex]\( -4, 6 \)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.